If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 = 5 + 2y Solving -9 = 5 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -9 + -2y = 5 + 2y + -2y Combine like terms: 2y + -2y = 0 -9 + -2y = 5 + 0 -9 + -2y = 5 Add '9' to each side of the equation. -9 + 9 + -2y = 5 + 9 Combine like terms: -9 + 9 = 0 0 + -2y = 5 + 9 -2y = 5 + 9 Combine like terms: 5 + 9 = 14 -2y = 14 Divide each side by '-2'. y = -7 Simplifying y = -7
| 3x^4-9x^3-1x^2=0 | | -335=-14x-125 | | (9-x)(9-x)=17 | | 166=2x-3(6x+18) | | 6x^2+14x-9x-21= | | 7r+4=2r+20 | | -4/9z=-3/5 | | 4x-9=5x+4 | | -48-14x=-202 | | 2ix^2+x+15i=0 | | 4.5=2x+3 | | 2x=429 | | 3-5n+3n=35-72 | | 5(x+7y)-8(6+y)= | | 60x^2+120x=0 | | -7+2x=9 | | X^5+36x=0 | | X^2+5x^2+4=0 | | 20-3x=5+2x | | x+x+8=26 | | x-5=1-2x | | -6(x+5)-44=2-22 | | 20x^3+60x^2=0 | | -11+2x=7 | | y+63x^3-75x^2+18x=0 | | 2(-2)+4y=-8 | | 2x-12+6x-21=6x+21 | | y=63x^3-75x^2+18x | | -5/6w=-16.5 | | 2*3.14x=44 | | 4(7b-8)+8=-3+7(7b+3) | | 0.5(x-8)=20 |